Errors in Forensic Ballistics: Causes and Elimination - A. V. Kokin (Теория и практика судебной экспертизы)
The article discusses problematic issues related to expert errors in forensic ballistics. The causes of procedural and implementation errors committed by investigators and forensic practitioners are examined, and ways to prevent and eliminate such errors are suggested.